Behavior based mobile robot vision for navigation - Mohammad S., Al-Khalifah Sami (2012)
This project focuses on the navigation strategies of multi-robot system. Most work on navigation strategies of multi-robot system has been empirical, with many navigation architectures having been proposed and validated. With the goal of bringing some objective grounding to this important area of research, this project presents a study in i-MARS. A domain-independent taxonomy of i-MARS problems is given. This project demonstrates how such theories can be used for analysis and greater understanding of the problems, and suggests how the same theory can be used in the synthesis of new approaches. Intelligent multi agent robot system (i- MARS) is a set of robots that can communicate between each other to complete certain task. This report presents a project on vision behavior based robot navigation strategy for a single robot that can be used in multi agent robot. The platform is given the name “UTM Multi agent robot’ is designed for research activity purpose and it has a great potential for future development.